2003
DOI: 10.1046/j.1523-1755.2003.00734.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal function and outcome of PTRA and stenting for atherosclerotic renal artery stenosis

Abstract: Patients with atherosclerotic RAS fulfilling strict criteria of severity may have significant improvements in BP one year after PTRAS but only modest in GFR. The initial GFR may anticipate whether the benefits in the outcome will be in renal function enhancement (those with an initially depressed GFR) or in hypertension control (those with an initially normal or mildly impaired GFR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 29 publications
1
43
0
Order By: Relevance
“…[27][28][29][30][31] For patients with a normal or mildly impaired renal function, however, it is unclear if and when intervention should be performed to prevent progressive renal failure, because the rate of progressive narrowing of the renal artery and the associated rate of progressive renal failure is generally slow. 32 Our study shows that intervention should not be postponed in patients with bilateral stenosis, even if their renal function is not impaired as yet.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31] For patients with a normal or mildly impaired renal function, however, it is unclear if and when intervention should be performed to prevent progressive renal failure, because the rate of progressive narrowing of the renal artery and the associated rate of progressive renal failure is generally slow. 32 Our study shows that intervention should not be postponed in patients with bilateral stenosis, even if their renal function is not impaired as yet.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the small number of patients involved in this study, the sample tried to select the cases with a clear clinical indication for percutaneous renal revascularization, either to control systemic hypertension or to preserve or restore renal function 3,12,20,21 . In fact, several studies have evaluated the renal function after renal angioplasty with stent placement 10,11,[16][17][18][20][21][22][23] . A study carried out by Jensen 24 evaluated 107 patients with ARAS in a one-year follow-up after stenting in renal artery and found that this group showed decreased BP and increased glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 99%
“…Renal USDoppler was used since it is sensitive to detect post-stenting renal artery stenosis 18,19 . The literature reports post-stenting renal artery stenosis rates of 15% 20 .…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that a stenosis of much greater severity is required to generate the renin, other mediators and hypertension from an affected kidney. A recent study from Ramos and colleagues 14 showed that when an arterial stenosis of 70% with a trans-lesion pressure gradient430 mm Hg was defined as the lower limit of significance, angioplasty offered a significant reduction in BP, with a modest increase in glomerular filtration rate. These data are from an observational study rather than a clinical trial but at least point the way towards the demonstration that relief of a severe stenosis may be of value.…”
Section: Discussionmentioning
confidence: 99%